1995
DOI: 10.1088/0022-3727/28/4/025
|View full text |Cite
|
Sign up to set email alerts
|

Tip-shape investigation of a Au-Si alloy liquid metal ion source using a high voltage transmission electron microscope

Abstract: The tip shape of a Au-Si liquid-metal ion source in terms of its dependence on the total ion emission current has been investigated in situ in the Halle 1 MeV electron microscope. Within the emission current range 7-90 mu A there is a linear dependence of the cone half-angle a and the length I of the jet-like protrusion on the increased emission current. The jet-like protrusion at the Taylor cone vertex was not so pronounced as has been observed in the cases of elementary liquid-metal ion sources. No spatial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…A similar behavior of ␣ with increasing current can be seen for AuSi15 and CoGe 19 LAIS FIG. The slope of the curve changes at a current of 20 A from Ϫ0.28 to Ϫ0.045 deg/A.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…A similar behavior of ␣ with increasing current can be seen for AuSi15 and CoGe 19 LAIS FIG. The slope of the curve changes at a current of 20 A from Ϫ0.28 to Ϫ0.045 deg/A.…”
supporting
confidence: 75%
“…There is a great effort to establish a theoretical model of these sources in order to understand the particle emission processes involved. The experimental results obtained with AuSi, 15 Ga, 16 In, 17 Sn, 18 and CoGe 19 ion sources gave evidence for a material dependence of the tip shape. [12][13][14] Therefore we have started a systematic in situ tip shape investigation of pure metal and alloy LMIS in the 1 MeV TEM at the Max-Planck-Institut in Halle.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Therefore Driesel et al observed Au-Si, 3 and Au-Ge LAISs 4 in operation in a 1 MeV scanning electron microscope. 1 and 2͒.…”
Section: Introductionmentioning
confidence: 99%
“…1 and 2͒. 3 Transmission electron microscopy ͑TEM͒ investigations on Ga, 5,6 In, 7 and Sn liquid metal ion sources ͑LMIS͒ 8 during ion emission facilitated the better understanding of the ion and microdroplet emission process from LMISs in a large range of ion current. Therefore Driesel et al observed Au-Si, 3 and Au-Ge LAISs 4 in operation in a 1 MeV scanning electron microscope.…”
Section: Introductionmentioning
confidence: 99%